Penciptaan, Kejatuhan Manusia dalam Dosa dan Puncak Sejarah Keselamatan pada Kristus dalam Perspektif Gereja - Hermawan, Peter (Felicitas, 2022)
The Nicene-Constantinople creed very clearly recognizes God the Father as the Creator of this universe. Man was created in the image of God, both male and female. According to Genesis 1:27 God created everything in this world really good and beautiful. Classical Creation Theology says that God created this world from something that did not exist before (creatio ex nihilo). The creation story in Genesis 1 illustrate that God created everything in this world in an orderly and systematic way. However, due to Adam's disobedience to God, humans who were originally created very noble and in the image of God experienced separation. As a result of this original sin, it lost the sanctity and justice of its nature when it was first created. But because of God's mercy, He gave God's only begotten Son, the Word of Truth, to save and redeem mankind from sin through His sacrifice on the cross. In order for humans to obtain that great salvation, humans must have faith in God who has given redemption through His Only Begotten Son, Jesus Christ. The manifestation of this faith is to receive the Sacrament of Baptism.